Water babies - Kingsley, Charles (Penguin, 1994)
When Tom, an ill-treated little chimney-sweep, jumps into a clear, cool stream to clean himself, something fantastical happens; he is turned into a tiny water baby by the fairies, and he enters a strange, magical underwater world.